Capital controls: A normative analysis - Bianca De Paoli; Anna Lipinska (Federal Reserve Bank of New York, 2013)
Countries' concerns about the value of their currency have been studied and documented extensively in the literature. Capital controls can be - and often are - used as a tool to manage exchange rate fluctuations. This paper investigates whether countries can benefit from using such a tool. We develop a welfare-based analysis of whether (or, in fact, how) countries should tax international borrowing. Our results suggest that restricting international capital flows through the use of these taxes can be beneficial for individual countries, although it would limit cross-border pooling of risk. The reason is because, while consumption risk-pooling is important, individual countries also care about domestic output fluctuations. Moreover, the results show that countries decide to restrict the international flow of capital exactly when this flow is crucial to ensure cross-border risk sharing. Our findings point to the possibility of costly capital control wars and thus to significant gains from international policy coordination.
Keywords: E61; F41; G15; 330; capital controls; welfare; international asset markets